THE FACTORS INFLUENCING THE WILLINGNESS TO BUY KOREAN NOODLES WITH MODERATING VARIABLE OF DOMESTIC PRODUCT JUDGEMENT - Cynthia Anna Wijayanti; Jessen Jessen (Journal of Global Business and Management Review, 2022)
This study aims to examine the effect of Consumer ethnocentrism and worldmindedness on willingness to buy imported Korean noodle. It is proposed that Domestic product judgement has a moderating effect toward willingness to buy imported Korean noodle. This research was using sampling method of non-probability purposive sampling collecting 115 respondents using distributed electronic questionnaires. Then, the data collected is tested and analysed using Structural Equation Model where the results showed that consumer ethnocentrism does not have negative effect on willingness to buy imported Korean noodle as proposed in H1, while world mindedness has a negative but insignificant effect on willingness to buy imported Korean noodle. The further findings suggested that domestic product judgement has no moderating effect on the relationship between consumer ethnocentrism and willingness to buy imported Korean noodle. However, the result showed that domestic product judgement proven to moderate the relationship between world mindedness and willingness to buy imported Korean noodle. The managerial implications provide several recommendations not only for domestic retailers but for importers especially in imported noodles as well.